RS Codes for Downlink LTE System over LTE-MIMO Channel - Ghasan Ali Hussain; Lukman Audah (Universitas Ahmad Dahlan, 2018)
Nowdays, different applications require a modern generation of mobile communication systems; long term evolution (LTE) is a candidate to achieve this purpose. One important challenge in wireless communications, including LTE systems, is the suitable techniques of controlling errors that degrade system performance in transmission systems over multipath fading channels. Different forward Error correction (FEC) techniqes are required to improve the robustness of transmission channels. In this paper, Reed-Solomon (RS) codes were used with a downlink LTE system over a LTE-MIMO channel. This research contributes by combining RS codes that have low decoding complexity (by using hard decision decoding) with a LTE-MIMO channel to improve downlink LTE system performance. The results show that using RS codes clearly improves LTE system performance and thus decreases Bit Error Rates (BER) more than convolutional and turbo codes which have high decoding complexity. Lastly, the results show also extra improvements of downlink LTE system performance by increasing the number of antennas of the LTE-MIMO channel.